KAJIAN SEMANTIK KATA ‘DAMAI SEJAHTERA’ DALAM BAHASA INDONESIA - Hendarto Supatra (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
There is no expression Damai Sejahtera in Kamus Besar Bahasa Indonesia. In this dictionary we can find the meaning of damai and the meaning of sejahtera. That proves that DS is not a word but a phrase. In fact DS is not difference with damai dan sejahtera. The phrase that found in the Bible (John 14, verse 27) and commonly used among Indonesian Christians get its equivalent peace in English Bible and tentrem rahayu in Javanese Bible. Peace that commonly translated damai in Indonesian si not true in Indonesian Bible. Damai Sejahtera discussed in this article got its original concept from ancient Christian society not from English. That must be the reason. Budhism use the word bahagia meaning spiritual bliss with a special meaning which is not exactly the same with that that is used among Christian. So beside its common meaning used and known by all Indonesian people, speakers of bahasa Indonesia, DS also has specific meanings among Indonesian subculture like Budhis community, Muslim community, Christian community, etc.